2019
DOI: 10.3390/ma12060908
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Endodontic Procedures Using Contemporary Endodontic Materials

Abstract: Calcium hydroxide apexification and Mineral Trioxide Aggregate (MTA) apexification are classical treatments for necrotic immature permanent teeth. The first tend to fail for lack of compliance given the high number of sessions needed; the second has technical difficulties such as material manipulation and overfilling. With both techniques, the root development is interrupted leaving the tooth with a fragile root structure, a poor crown-to-root ratio, periodontal breakdown, and high risk of fracture, compromisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 173 publications
4
72
0
3
Order By: Relevance
“…Silicate-based hydraulic biomaterials, categorized as bioactive endodontic cements (BECs), emerged as bright candidates for the coronal sealing of the previously established blood clot scaffold [22]. These non-resorbable biocompatible materials have shown bioactive properties in direct contact with dental pulp stem cells (DPSCs) using in vitro assays [23].…”
Section: Introductionmentioning
confidence: 99%
“…Silicate-based hydraulic biomaterials, categorized as bioactive endodontic cements (BECs), emerged as bright candidates for the coronal sealing of the previously established blood clot scaffold [22]. These non-resorbable biocompatible materials have shown bioactive properties in direct contact with dental pulp stem cells (DPSCs) using in vitro assays [23].…”
Section: Introductionmentioning
confidence: 99%
“… 29 MTA is the most material used for coronal barrier 10 due to its beneficial properties, as good sealing ability, low cytotoxicity, antimicrobial effect, biocompatibility and ability to induce proliferation of stem cells from apical papilla. 30 …”
Section: Discussionmentioning
confidence: 99%
“… 4 , 15 For some time, the use of calcium hydroxide in pulp revascularization was not indicated due to its high pH and the possible tissue necrosis, preventing the differentiation of mesenchymal cells into new vital tissue. 30 However, more recent studies showed that calcium hydroxide can be recommended in pulp revascularization. 5 , 37 , 38 In addition to its property of microbial reduction and to the fact that it does not have the potential for crown discoloration, it also does not exhibit cytotoxicity to stem cells of the apical papilla, increases the release of dentin growth factors by EDTA, provides a better environment for attachment of viable apical papilla cells on dentin and does not cause bacterial resistance, as it can happen if there is a random use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Despite not knowing the real reason for the failure, there are some hypotheses like the presence of bacteria in the apical part of the root. Another possibility is the disruption of the blood clot, leaving an empty space inside the canal and no proper coronal seal [2,10,12,[14][15][16][17]. When a REP is confirmed as unsuccessful, alternative treatments must be considered such as apexification with MTA.…”
Section: Discussionmentioning
confidence: 99%